PENGARUH KEWIRAUSAHAAN DAN KECERDASAN EMOSI TERHADAP PRODUKTIVITAS KERJA ETNIS TIONGHOA PADA INDONESIA CHINABUSINESS COUNCIL (ICBC) SUMATERA SELATAN - Irsan - (Jurnal Media Wahana Ekonomika, 2016)
This research is aimed at analyzing the effect of entrepreneurship together with emotional intelligence to the working productivity of Tionghoa ethnic at Indonesia China Business Council (ICBC) South Sumatera. This research was conducted for all management and members at Indonesia China Business Council (ICBC) South Sumatera and the population was 93 respondents. From the 93 questioners that were distributed to the respondents, only 87 questioners were returned to the researchers, and 6 respondents were not. The data were analyzed by using validity and reliability tests, and factor analysis. Then it was done by using classic assumption and double linear regression analysis. To see the partial correlation, t-test and F-test were used to see the simultaneous correlation.The result shows thatentrepreneurship together with emotional intelligenceeffects the working productivity of Tionghoa ethnic at Indonesia China Business Council (ICBC) South Sumatera significantly. Keywords : Entrepreneurship, Emotional Intelligence, and Work Productivity.